Passengers’ Willingness to Pay for Carbon Offsetting in Thailand’s Aviation Sector: Evidence from Full-Service Airlines - Laphet, Jakkawat; Amnuaycheewa, Sukit; Tandamrong, Duangrat (International Journal of Energy Economics and Policy, 2026)
This study investigates passengers’ willingness to pay for carbon offsetting within Thailand’s aviation sector, with a focus on full-service airlines. Employing a quantitative methodology, a structured questionnaire was distributed to 400 passengers, and data were analyzed using Structural Equation Modeling (SEM). The results indicate that greater environmental knowledge and concern significantly increase the willingness to pay, with an average rate of 85.97%. Additionally, passengers who have a strong connection to nature and hold positive environmental attitudes are more likely to sup-port carbon offset programs. Key recommendations include enhancing environmental awareness through targeted educational campaigns, providing transparent information about offset options, establishing effective communication channels, and collaborating with environmental organizations. By implementing these strategies, airlines can im-prove passenger engagement in sustainability initiatives, encourage responsible travel behaviors, and support the long-term sustainability of the aviation industry.